ANALISIS KOMODITI JAGUNG (ZEA MAYS L) - Asmina Herawaty Sinaga (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2018)
Energy Competitiveness Analysis of Corn Products (Zea Mays L). The research procedure is Private Profitability (PP): D= A–( B+C) If D 0, means that the goods system gains profit from natural payments if the goods can grow, but if the source of energy is limited or there are substitutes that are more profitable. Social Profitability (SP): H= E–(F+G) Social profit is a marker of the comparative advantage of the goods system in a situation where there is no good comparison due to the effects of the ruler's discretion or market bias. The results of this research are multiple profitability (PP) = D = 7,099, 980. Nominal Protection Coefficient on Input (NPCI) = B or F = 0. 6610 < 1 meaning that there is a policy of focusing on tradable inputs. View Transfer( FT) = C- G = 0 means there is no transfer from farmers to producers of non tradable inputs. Effective Protection Coefficient(EPC)=(A-B) or(E or F)= 0.814 < 1 to conclude that the policy is not protective. Transfer net( NT)= D- H= 1. 622. 342 > 0 means that there is an additional producer surplus due to the impact of the government's policies on agricultural goods in the country. Profitability Coefficient (Computer) = D or H = 0.814 > 0 meaning that the government's policy has not distributed incentives to producers. Ratio to Producer (SRP) = L or E = 1,622,342 or 18,391,130 = 0.0882 meaning that if the family relationship income at social value for the exchange policy is very small. Corn farming in research has been efficient.